In search for Gonipterus platensis (Marelli, 1926) (Coleoptera: Curculionidae) egg parasitoids in Antioquia, Colombia (2019)
The eucalyptus snout beetle, Gonipterus spp. are a pest of Eucalyptus stands in the world causing serious economic loses. Gonipterus platensis (Figure 1) was ¬rst reported in Antioquia (Colombia) in 2016, by the Instituto Colombiano Agropecuario –ICA (ICA, 2016), threatening more than 60.000 ha planted with eucalyptus around the country. Classical biological control of these species has worked in some countries using the egg parasitoids Anaphes nitens (Girault) and Anaphes inexpectatus Huber & Prinsloo, 1990 (Hymenoptera: Mymaridae) and complemented with di erent natural enemies (NE) in some countries (Nascimento et al. 2017). A. nitens had been reported with high e cency ¬nding G. scutellatus egg masses reaching a parasitism rate of 80–100% of eggs in North west Spain (Rivera et al. 1999). It is necessary to know Gonipterus platensis NE, including the presence of A. nitens and A. inexpectatus, in local conditions so integrated pest management programs could be designed. This is the ¬rst survey of the NE for G. platensis in Colombia.